Recent developments towards enhancing process safety: Inherent safety and cognitive engineering. (2nd September 2019) - Srinivasan, Rajagopalan; Srinivasan, Babji; Iqbal, Mohd Umair; Nemet, Andreja; Kravanja, Zdravko
Abstract: Safety is paramount aspect of any chemical plant. In this paper various approaches to enhance process safety are evaluated. The specific enhancements include process design methodologies for improving inherent safety and cognitive engineering to reduce human errors. Their aim is to reduce the number and the consequences of possible deviation events, which depends predominantly on quality of the equipment and human error potential. The consequences are linked to the substances and their inventories. An inherent safety index is used to assess the properties of substances and process units while the potential for human error is characterized using various physiological measures. Our research indicates that application of process synthesis methodologies for simultaneous inherent safety assessment and advanced cognitive engineering approaches for human error reduction will lead to enhanced process safety.